Online language education courses: a Chinese case from an ecological perspective - Mei Fang; Lu Yunru; Ma Qing (Journal of China Computer-Assisted Language Learning)
In this study, we examined the usefulness of and students’ perceptions of a one-to-one online oral EFL course. Based on van Lier’s learning theory of ecology, we studied the positive aspects that encouraged learning and the negative aspects that required improvement. A total of 18 young-adult English learners from different parts of China were invited to attend three one-to-one (teacher–learner) online lessons designed by the researchers. A quasi-experimental one-group design was used to examine the effectiveness of the online course. In addition, an online survey and semi-structured individual interviews were conducted to reveal the learners’ views and perspectives on the course. The results indicated that the participants made good progress in terms of complexity in oral skills and perceived the course to be highly useful, especially regarding opportunities to express personal views, timely scaffolding, and efficient feedback from the teacher. Based on the findings, a number of implications for improving the course are provided, in addition to suggestions for a better one-to-one online oral English course model.